Saving women and bordering Europe: narratives of "Migrants' Sexual Violence" and geopolitical imaginaries in Russia and Sweden. Issue 3 (26th May 2020) - Edenborg, Emil
ABSTRACT: This article maps the specific ways in which gendered and racialized boundary constructs create conditions of possibility for certain bordering practices. Connecting Critical Border Studies with feminist theories of geopolitics, it examines media reporting in Russia and Sweden about "migrants' sexual violence" in the wake of the 2015 New Years' events in Cologne. Despite contextual differences, in both countries these events were narrated as symbolic in negotiating Europe and its borders. In Russia, the events were connected to a story of a Russian girl in Berlin being raped by migrants (a story later revealed to be fabricated) and a narrative of Europe collapsing because of immigration. In Sweden, the events were connected to reports of sexual violence at festivals, sparking a debate about "Swedish values" of gender equality being endangered by immigration. The article argues, firstly, that narratives of migrants' sexual violence performed bordering functions in both the symbolic sense of delineating national identity and Europeanness, and the concrete sense of legitimating a stricter border regime. Secondly, it argues that the narratives performed that function only by tapping into local geopolitical narratives, in the Russian case on the country's ambivalent relation to Europe, and in Sweden the idea of gender exceptionalism.